Garden Tourism and Sustainable Development in the Region of Mekong Delta - Nguyen Tan Danh (International Journal of Advanced Science and Technology, 2020)
Considered as a key economic region by many advantages in developing agriculture andtourism, peasant life in Mekong Delta region still faces many difficulties. However, alongwith the development of the country, the rural areas have gradually changed with a newface from material life to spiritual life of the people. And for sustainable development ofthese rural areas, it is a big challenge for localities in particular and Vietnam in general.In order to develop the economy, horticultural tourism has long been considered one ofthe solutions to contribute to increasing incomes and improving the lives of rural people.At the same time, the ecological environment is guaranteed and is one of the key goals foreconomic development. This type of tourism is not new, but its difficulties, challenges aswell as advantages need to be carefully and surely analyzed.